The role of psychological service in human life - Timur Sattorov Sobirovich (Genius Journals, 2023)
This article provides information on the role of psychological services in human life, mental health support, counseling and therapy, emotional support, behavior change, and skill development
Keywords: Psychological services; daily activities; emotions